The differentiation state of small intestinal organoid models influences prediction of drug-induced toxicity - Klein, Jessica A.; Heidmann, Julia D.; Kiyota, Tomomi; Fullerton, Aaron; Homan, Kimberly A.; Co, Julia Y. (Frontiers in Cell and Developmental Biology, 2025)
Drug-induced intestinal toxicity (GIT) is a frequent dose-limiting adverse event that can impact patient compliance and treatment outcomes. In vivo, there are proliferative and differentiated cell types critical to maintaining intestinal homeostasis. Traditional in vitro models using transformed cell lines do not capture this cellular complexity, and often fail to predict intestinal toxicity. Primary tissue-derived intestinal organoids, on the other hand, are a scalable Complex in vitro Model (CIVM) that recapitulates major intestinal cell lineages and function. Intestinal organoid toxicity assays have been shown to correlate with clinical incidence of drug-induced diarrhea, however existing studies do not consider how differentiation state of the organoids impacts assay readouts and predictivity. We employed distinct proliferative and differentiated organoid models of the small intestine to assess whether differentiation state alone can alter toxicity responses to small molecule compounds in cell viability assays. In doing so, we identified several examples of small molecules which elicit differential toxicity in proliferative and differentiated organoid models. This proof of concept highlights the need to consider which cell types are present in CIVMs, their differentiation state, and how this alters interpretation of toxicity assays.